BALKANS (AND WESTERN BALKANS) AS NEGATIVE POLITICAL TERMS - Đorić, Marija (National interest, 2024)
The paper analyzes the negative perception of the Balkans, with special reference to the Western Balkans, as a newly introduced political concept. The author explains the historical and political environment through which the negative image of the Balkans is built, indicating that this region was separated and precipitated as "otherness" in relation to Europe. Based on that analogy, the author explains how the Western Balkans now find themselves in a position of "otherness" in relation to the rest of the Balkan countries (which have become articles of the EU). The violent past, the "curse of small differences" and unresolved political conflicts make the Western Balkans a problematic region under the watchful eye of major powers. The point where the interests of all the countries of the Western Balkans can coincide is European integration, which indicates the "common destiny" of this region.
Keywords: Balkans; Western Balkans; balkanization; Serbia; EU; politics; violence